Crianças no espaço urbano: um estudo sobre políticas públicas no contexto das "cidades amigas da criança" - Bertuol, Carla (2008)
This research addresses the relationships between children and the cities within the public policies aimed at to transform the cities in good environments for children. From a constructionist stance, we consider that the current universal definition for child taken for granted derived from the segregation of children from the social life space and the construction of due specific places as ways for the modern rationality wield control over the experience of being child. The Federal Constitution of 1988 proposed an agenda dedicated to the childhood in the public policies of brazilian cities, within the political-administrative decentralization trend or municipalization processes and afterwards within the Child and Adolescent Statute of 1990. In this agenda some peculiar voluntary initiatives of evaluation and award are proposed for the cities that develop public policies pointed to this issue and also a possibility of registration in the Child Friendly Cities initiative of the United Nations Organization. We understand the public policies as the government s ways to make choices about public actions to be implemented and we start from the presupposition that despite of the hegemonic conceptions about children, if we look to the city as a place, looking at children s presence in the city and his/hers relationships with public policies practices, we can contribute so that their positions and resistance possibilities become more visible, expanding the dialogue between children and public policies. The theory that we present here is that the cities, when organized based in universalistic assumptions about the childhood, bring forth a vision of the adults over the children into the public policies, and that in the daily practices, children take the urban space using it as resistance forms. This study pursues two objectives. The first one to discuss how the public policies guided by the child s friend initiative presuppositions deals with the children s specificities, considered as social authors and actors we have approached the field-theme through dialogues with the decision makers of the municipal public policies, followed up the meetings of the municipal facilities Little Net , made interviews and took part in events accomplished in Santo André- SP. For the second objective to know the resistance strategies of the children in relation to the actions emanated from those policies - we have accomplished unstructured observations on the use of the urban space by children and we observed them within a programmatic action, the Expresso Lazer. We found that the adult vision about children in organizational forms devoted to warrant children s rights are hegemonic and that any consideration from the children about the use of the urban space doesn t enter among the possibilities for solving the issues discussed there, resulting in an approach that is usually far from the experience of being child. We also found out that children actively attempt to build his/her presence close to the daily life together with the adults, and in this enthusiasm they show auto-organization capacity and autonomy in the use of the space, an don t show their selves malleable to the dominance forces reacting with resistance in the use of urban space. In the final considerations we discuss how children s rights have potential for transformational in the child s friend cities context and we suggest dialogue possibilities within Social Psychology